The Influence of Cross Culture on Teaching Civilization A survey on 3rd year Students and Teachers of English at Laghouat University - SAFI, Chahrazede; Hachani ,Siham (Faculty of Letters and Foreign Languages Department of English, 2018)
At present, cross-cultural communication has become important; the teaching of civilisation at the EFL Department is supposed to improve students’ intercultural skills. This study aims at investigating whether or not teachers of civilisation integrate culture, and what are the appropriate techniques and materials they use in teaching. The method used in this study includes students and teachers' questionnaires, and classroom observation, where students' interaction with teachers is taken into consideration, also their attitudes and views about the techniques and materials their teachers use in class. It also included teachers' view about teaching culture and civilisation. The findings of this research have shown that teachers of civilisation dealt with the main cultural aspects when teaching civilisation. They also have revealed that the way of teaching culture requires appropriate materials and techniques in order to integrate culture in teaching civilisation properly